Early DIRECT mode decision based on all‐zero block and rate distortion cost for multiview video coding. Issue 1 (1st January 2016) - Pan, Zhaoqing; Zhang, Yun; Lei, Jianjun; Xu, Long; Sun, Xingming
Abstract : The exhaustive variable‐block‐size mode decision can efficiently remove the redundancies among the multiview videos, while it also leads to significant increase of computational complexity in the multiview video coding (MVC) encoder, and the high encoding complexity becomes a bottleneck for the MVC encoder to achieve real‐time multimedia applications. To address this bottleneck, many fast mode decision methods have been proposed. However, most of them are only suitable for optimising the encoding complexity of the odd views of the MVC encoder. In this study, based on the property of the all‐zero block and rate distortion (RD) cost of the DIRECT mode as well as the correlations between the current macroblock (MB) and its spatial–temporal nearby MBs, an early DIRECT mode decision method is proposed for reducing the encoding complexity of the MVC. Experimental results show that the proposed method achieves 48.25 and 55.64% on average encoding time saving for the even and odd views, respectively, whereas the RD performance degradation is quite acceptable. In summary, the proposed method efficiently reduces the encoding complexity for the MVC encoder.